2005
DOI: 10.1179/016164105x18494
|View full text |Cite
|
Sign up to set email alerts
|

Variation in nerve autograft length increases fibre misdirection and decreases pruning effectiveness. An experimental study in the rat median nerve

Abstract: Variation in the length of nerve grafts interferes in behavioural recovery and increases motor fibres misdirection. Early recovery onset was related to a better outcome, which occurs in the short graft group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
1
20
1
1
Order By: Relevance
“…In addition to the axonal misalignments at the proximal and distal coaptation sites, the regenerating axons would grow aberrantly throughout the grafts. 5,6 In those cases, it would be beneficial to employ prosthetic tubulization. We expected that an impermeable conduit placed at the distal end of the nerve graft might correct, at least partly, the axonal misdirection by gradual axon dispersion within the closed space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the axonal misalignments at the proximal and distal coaptation sites, the regenerating axons would grow aberrantly throughout the grafts. 5,6 In those cases, it would be beneficial to employ prosthetic tubulization. We expected that an impermeable conduit placed at the distal end of the nerve graft might correct, at least partly, the axonal misdirection by gradual axon dispersion within the closed space.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such ideal fascicular grafts are rarely available in the clinical setting, thereby resulting in aberrant projections at both proximal and distal coaptation sites. 5 Moreover, as it has been suggested that the regenerating axons become aberrant throughout the nerve graft length, 5,6 the graft length itself would also increase axonal misdirection.…”
mentioning
confidence: 98%
“…The basic mechanism leading to poor recovery appears to be related to increased fiber misdirection and defective pruning in longer grafts. 25 The accessory nerve is pure motor and innervates, distal to the repair site, a single muscle. Fiber misdirection probably exists to a lesser extent, thereby having a smaller effect on recovery; this explains the good results we obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In general, regeneration through shorter grafts is better. 13 In brachial plexus repairs, however, short grafts are connected to the divisions of the brachial plexus, rather than to the terminal branches. This may decrease the success of reconstruction, because of dispersion of the regenerating nerve fibers, a well-known concept among brachial plexus surgeons.…”
Section: Elbow Motionmentioning
confidence: 99%